Application value of multiparametric MRI for evaluating iron deposition in the substantia nigra in Parkinson's disease - Cao, Qing; Huang, Jinjin; Tang, Dongping; Qian, Hao; Yan, Kun; Shi, Xun; Li, Yaowei; Zhang, Jiangong (Frontiers in Neurology, 2023)
[Objective] This study aimed to investigate the application value of multiparametric magnetic resonance imaging (MRI) in the diagnosis of iron deposition in the substantia nigra dense zone in Parkinson’s disease (PD) and to evaluate the diagnostic value of the correlation among multiparametric imaging indicators, clinical stage, and disease duration. [Materials and methods] Thirty-six patients with clinically confirmed PD and 36 healthy controls were enrolled.All subjects underwent magnetic sensitivity weighted imaging (SWI), neuromelanin magnetic resonance imaging (NM-MRI), and a T2*mapping sequence. Based on the fusion of the NM-MRI and SWI amplitude maps, phase maps, and T2*MAPPING value maps, NM-MRI was used to delineate the dense zone of the substantia nigra, which was divided into three subregions: upper, middle, and lower. In this way, the amplitude, phase, and R2* values of each subregion and the average value of the sum of the three subregions were obtained simultaneously in the SWI amplitude, phase, and T2*MAPPING maps. The multiparameter imaging indices were compared between the two groups, and the correlation between them and clinical indices was evaluated in the PD group. [Results]The upper (amplitude, phase value, R2* value), middle, and lower (amplitude) right substantia nigra compact zones were significantly different between the PD and control groups. The upper (phase value, R2* value) and middle (amplitude) areas of the left substantia nigra compact zone were also significantly different between the two groups (all P<0.05).. Amplitudes of the middle and lower parts of the dense zone of the left substantia nigra were negatively correlated with the H-Y grade (middle: r=-0.342, P=0.041; lower: r=-0.399, P=0.016). The average amplitude of the right substantia nigra compact zone was negatively correlated with the H-Y grade (r=-0.367, P=0.027). The average R2 * value of the compact zone of the left substantia nigra was positively correlated with the H-Y grade (r=0.345, P=0.040). [Conclusion] Multiparametric MRI sequence examination has application value in the evaluation of iron deposition in the dense zone of the substantia nigra in PD. Combined with NM-MRI, fusion analysis is beneficial for accurately locating the substantia nigra compact zone and quantitatively analyzing the iron deposition in different subregions.